STRUCTURE OF THE EARTH'S CRUST AND UPPER MANTLE WITHIN KIMBERLITE AND OIL AND GAS FIELDS - Egorkin A.V. (My University, 2003)
The structure of the crystalline crust (CC) and the mantle was studied to a depth of 700 km by seismograms of chemical and nuclear explosions under kimberlite and oil and gas fields. Both types of fields are located in close contact with blocks of the CC with anomalous SiO2 content: the first one in contact with blocks of intermediate and basic composition and the second one in contact with blocks of intermediate and acid composition. Diamond fields are confined to higher temperature areas of the transitional upper mantle-lower mantle layer, and oil and gas fields, to lower temperature areas. Irrespective of this fact, it is possible to recognize the similarity of processes resulting in the formation of diamond and hydrocarbon fields. The mineral type is dominated by the temperature of the transitional mantle zone: hydrocarbons are formed at lower temperatures (low oxygen volatility), and diamonds are generated at higher temperatures.